Pengaruh Model Pembelajaran Problem Based Learning (PBL) Berbantuan Media Pop Up Book terhadap Partisipasi Aktif Siswa pada Materi Ekosistem Kelas X di SMA Islam Samarinda - Nurhidayah Eka Widyaningrum; Masitah Masitah; Zenia Lutfi Kurniawati; Jailani Jailani; Herliani Herliani; Vandalita Maria Magdalena Rambitan; Suparno Putera Makkadafi (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
Active student participation is the direct involvement of students in the learning process which includes indicators, such as: giving opinions, giving responses, doing assignments, concluding, and presenting. Class X students at SMA Islam Samarinda have low active participation in learning activities. Therefore, the use of appropriate learning models and media is very necessary to attract students' attention so that students are more actively involved in learning activities. This study aims to determine the effect of the Problem Based Learning (PBL) learning model assisted by pop-up book media on students' active participation in ecosystem material for class X at SMA Islam Samarinda. The type of research used is quantitative research with a quasi-experimental method and uses a research design, namely pretest-posttest control group design. The sample in this study was class X-1 as an experiment and class X-2 as a control, where each class consisted of 25 students, so that the total sample was 50 students, with a sampling technique of simple random sampling. Data collection in this study used a student active participation questionnaire, with data analysis using a hypothesis test using an independent sample t-test with a significance level of 5%. Based on the research conducted, a 2-tailed significance value of 0.000 < 0.05 was obtained, indicating that the Problem-Based Learning (PBL) model using pop-up books significantly influenced student active participation in ecosystems material for 10th grade students at SMA Islam Samarinda.